2007
DOI: 10.1159/000109768
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Antibiotic Resistance Patterns of <i>Salmonella enterica</i> from Southwestern Greece

Abstract: Background: A study was conducted at the University Hospital of Patras between January 2002 and December 2003 to investigate antibiotic resistance patterns and clonality of Salmonella enterica in southwestern Greece. Methods: Ninety-five isolates recovered from different outpatients were characterized by specific antisera and were tested for their susceptibility to various antimicrobial agents. Clones were identified by pulsed-field gel electrophoresis (PFGE) of XbaI chromosomal DNA digests. Results: Five sero… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…In our hospital alone, there were about 150e200 reported cases each year. The seasonal variation of salmonellae in Hong Kong was similar to that reported in Europe, 15 with the number of cases of salmonellosis increasing from AprileMay and decreasing after AugusteSeptember as hot and humid weather provided an optimum environment for the salmonellae to grow on food and thus more cases during this time of the year. S. Enteritidis is the most common serovar isolated followed by S. Typhimurium, both of which were responsible for more than half of all salmonellosis cases each year.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In our hospital alone, there were about 150e200 reported cases each year. The seasonal variation of salmonellae in Hong Kong was similar to that reported in Europe, 15 with the number of cases of salmonellosis increasing from AprileMay and decreasing after AugusteSeptember as hot and humid weather provided an optimum environment for the salmonellae to grow on food and thus more cases during this time of the year. S. Enteritidis is the most common serovar isolated followed by S. Typhimurium, both of which were responsible for more than half of all salmonellosis cases each year.…”
Section: Discussionsupporting
confidence: 75%
“…15 In contrast, it might show that PFGE analysis might not be powerful enough to discriminate between strains. Recently, other typing methods, namely multiple-locus variable-number tandemrepeat analysis (MLVA) and multilocus sequence typing (MLST), have been used to type salmonellae.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Enteritidis serovar was not assessed by PFGE because, according to the literature, these isolates have low clonal diversity (Spiliopoulou et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In this study, the prevalence of Salmonella Enteritidis was 54%, which showed the dominance of this serovar in Iran. Recent reports from Brazil, Poland, Malaysia, China and Greece have shown the same serovar as the dominant serovar with the frequencies ranging from 34% to 86%, which reveals a coincident rise of this serovar around the world [15] , [16] , [17] , [18] , [19] .…”
Section: Discussionmentioning
confidence: 99%